Towards a knowledge-based organizational culture – discussion on empirical studies - Pietruszka-Ortyl, Anna (Management and Administration Journal, 2019)
The starting point of this paper is characteristic of the essence of organizational pathologiesand dysfunctions. This discussion is a contribution of deliberation on the development of an optimalorganizational culture - permitting the acquisition and maintenance of key employees. The present publicationpresents the results of empirical research regarding dysfunction and the pathology of the organizationalculture of enterprises in Poland. 195 respondents were examined whose opinions were interpretedin the context of the challenges of creating a model, in terms of the knowledge economy, types of organizationalculture - a culture based on knowledge, a culture of trust and a culture of cooperation.